The reorganization of root anatomy and ultrastructure of syncytial cells in tomato (Lycopersicon esculentum Mill.) infected with potato cyst nematode (Globodera rostochiensis Woll.) - Sylwia Fudali; Władysław Golinowski (Acta Societatis Botanicorum Poloniae, 2011)
The sequence of anatomical and ultrastructural events leading to the syncytium development in tomato roots infected with Globodera rostochiensis was examined. The syncytia were preferentially induced in cortical or pericyclic cells in the elongation zone of root. They developed towards the vascular cylinder by incorporation of new cells via local cell wall breakdown. After surrounding primary phloem bundle and reaching xylem tracheary elements syncytia spread along vascular cylinder. Roots in primary state of growth seemed to be the best place for syncytium induction as syncytia formed in the zone of secondary growth were less hypertrophied. At the ultrastructural level syncytial elements were characterized by strong hypertrophy, breakdown of central vacuole, increased volume of cytoplasm, proliferation of organelles, and enlargement of nuclei. On the syncytial wall adjoining vessels the cell wall ingrowths were formed, while the syncytial walls at interface of phloem were considerably thickened. They lacked of functional plasmodesmata and did not form any ingrowths. Using immunofluorescent-labelling and immunogold-labelling methods tomato expansin 5 protein was localized in nematode infected roots. The distribution of LeEXP A5 was restricted only to the walls of syncytia. The protein distribution pattern indicated that LeEXP A5 could mediates cell wall expansion during hypertrophy of syncytial elements.